2011
DOI: 10.1107/s0907444911006044
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Greyhound hemoglobin: origin of high oxygen affinity

Abstract: This study presents the crystal structure of Greyhound hemoglobin (GrHb) determined to 1.9 Å resolution. GrHb was found to crystallize with an α₁β₁ dimer in the asymmetric unit and belongs to the R2 state. Oxygen-affinity measurements combined with the fact that GrHb crystallizes in the R2 state despite the high-salt conditions used for crystallization strongly indicate that GrHb can serve as a model high-oxygen-affinity hemoglobin (Hb) for higher mammals, especially humans. Structural analysis of GrHb and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…We recently conducted additional studies on high‐affinity HGB and its function in RRGs, using blood gas analysis with cooximetry and confirmed low P 50 and higher oxygen content and oxygen‐binding capacity of HGB in Greyhounds . In a different study, we found that HGB in Greyhounds has a few unique amino acid mutations that are relevant to the oxygen affinity properties, and alter the position of the globin chains . Overall, HGB sequence in Greyhounds is closer to the human sequence than the equine or bovine sequences; thus, it may be used as a model for HGB of high‐oxygen affinity in people …”
Section: Literature Reviewmentioning
confidence: 70%
See 2 more Smart Citations
“…We recently conducted additional studies on high‐affinity HGB and its function in RRGs, using blood gas analysis with cooximetry and confirmed low P 50 and higher oxygen content and oxygen‐binding capacity of HGB in Greyhounds . In a different study, we found that HGB in Greyhounds has a few unique amino acid mutations that are relevant to the oxygen affinity properties, and alter the position of the globin chains . Overall, HGB sequence in Greyhounds is closer to the human sequence than the equine or bovine sequences; thus, it may be used as a model for HGB of high‐oxygen affinity in people …”
Section: Literature Reviewmentioning
confidence: 70%
“…In a different study, we found that HGB in Greyhounds has a few unique amino acid mutations that are relevant to the oxygen affinity properties, and alter the position of the globin chains . Overall, HGB sequence in Greyhounds is closer to the human sequence than the equine or bovine sequences; thus, it may be used as a model for HGB of high‐oxygen affinity in people …”
Section: Literature Reviewmentioning
confidence: 87%
See 1 more Smart Citation
“…Our structural analyses do not exclude the possibility that differences in ligand-binding affinity may result in part from amino-acid differences between and globin at any of several other positions. We note, for example, the change from Pro to Ala at position 119 of the -globin chain would be predicted to weaken hydrophobic interactions with s Met55 at the 1 s 1 interface and to consequently destabilize the T state (Bhatt et al, 2011), consistent with the effect of a similar amino-acid substitution on the O 2 affinity of the hemoglobin expressed by bar-headed geese (Zhang et al, 1996). Additional studies will certainly be required to fully account for the relative contribution of this and other candidate amino-acid differences to the ligand-binding affinities of heterotetramers containing -globin subunits.…”
Section: Hb F 2 B 2 S Exhibits a High Ligand Affinity That Is Weakly mentioning
confidence: 89%
“…R, RR2, R2 or R3) (Safo et al, 2004(Safo et al, , 2011Jenkins et al, 2009;Safo & Abraham, 2005;Mueser et al, 2000;Silva et al, 1992;Schumacher et al, 1995Schumacher et al, , 1997Janin & Wodak, 1993), in contrast to the quaternary tense structure described here. Moreover, a number of different relaxed structures can be obtained for heterologous hemoglobins using high-salt methods and in some instances using both high-salt and low-salt conditions (Safo et al, 2004(Safo et al, , 2011Jenkins et al, 2009;Safo & Abraham, 2005;Mueser et al, 2000;Silva et al, 1992;Schumacher et al, 1995Schumacher et al, , 1997Janin & Wodak, 1993;Bhatt et al, 2011), consistent with NMR evidence that the various relaxed structures, including the classical R structure, exist in nature in an ensemble of states (Lukin et al, 2003), and that Hb function involves such an ensemble of relaxed hemoglobin states in dynamic equilibrium (Safo et al, 2011;Jenkins et al, 2009;Safo & Abraham, 2005). These observations indicate that the high- Stereoview of interactions associated with the -(-) and -subunit C-termini in the T (PDB entries 2hhb or 2dn2; cyan), R (PDB entries 1aj9 or 1ljw; red), Hb 2 2 s ABCD (yellow) and/or EFGH (gray) structures.…”
Section: Discussionmentioning
confidence: 99%